(untitled) (Research, Society and Development, 2021)
Free-living Columbidae are considered the second largest reservoir of Chlamydia psittaci, transmitting the agent to humans and other animals. The present study aimed to identify the presence of Chlamydia spp. in samples of lung and stool collected from free-living domestic pigeons (Columba livia domestica) captured at the Mangal das Garças Naturalistic Park in Belém, Pará, Brazil, using semi-nested polymerase chain reaction, and also correlate the clinical and post-mortem findings of animals positive for Chlamydia spp. Among the 45 animals analyzed, 10 (22.2%) were positive for Chlamydia spp.; the positive findings originated from 5 (50%) lung samples and 5 (50%) stool samples, with no overlap between animals and samples. None of the animals evaluated in this study showed clinical signs of chlamydiosis; rather, these were only found during necropsy of positive animals, mainly through pulmonary, hepatic, splenic, and intestinal changes. These findings demonstrate that free-living pigeons can be reservoirs of Chlamydia spp. and transmit the agent silently to humans and animals, which is concerning for public and animal health, since these birds are easily found in urban areas cohabitating with humans, other species of birds, and other animals.